Potential Predictability of Net Primary Production in the Ocean. Issue 6 (8th June 2020) - Krumhardt, K. M.; Lovenduski, N. S.; Long, M. C.; Luo, J. Y.; Lindsay, K.; Yeager, S.; Harrison, C.
Abstract : Interannual variations in marine net primary production (NPP) contribute to the variability of available living marine resources, as well as influence critical carbon cycle processes. Here we provide a global overview of near‐term (1 to 10 years) potential predictability of marine NPP using a novel set of initialized retrospective decadal forecasts from an Earth System Model. Interannual variations in marine NPP are potentially predictable in many areas of the ocean 1 to 3 years in advance, from temperate waters to the tropics, showing a substantial improvement over a simple persistence forecast. However, some regions, such as the subpolar Southern Ocean, show low potential predictability. We analyze how bottom‐up drivers of marine NPP (nutrients, light, and temperature) contribute to its predictability. Regions where NPP is primarily driven by the physical supply of nutrients (e.g., subtropics) retain higher potential predictability than high‐latitude regions where NPP is controlled by light and/or temperature (e.g., the Southern Ocean). We further examine NPP predictability in the world's Large Marine Ecosystems. With a few exceptions, we show that initialized forecasts improve potential predictability of NPP in Large Marine Ecosystems over a persistence forecast and may aid to manage living marine resources. Plain Language Summary: Marine net primary production (NPP) is the base of the marine food web, as well as an important component of the ocean carbon cycle. Year‐to‐year variations in NPP can influence the availability of living marine resources, such as fish. In this study, we show that an Earth System Model can be used to generate near‐term (1 to 10 years) forecasts of marine NPP. Earth System Model‐based forecasts of NPP show an improvement over a persistence forecast, where NPP the following year is assumed to be the same as the current year's NPP. Annual NPP variations can be predicted for 1 to 3 years in advance in many oceanic regions, from temperate waters to the tropics. NPP in colder regions, however, is harder to predict. The main drivers of NPP influence its predictability. Places where nutrient availability primarily drives variations in NPP are more predictable than regions of the ocean where light and temperature are the main drivers (primarily high latitude regions). We further demonstrate NPP predictability in coastal regions, the world's Large Marine Ecosystems. We show that NPP predictions could be potentially useful in many Large Marine Ecosystems, and this may help to sustainably manage coastal marine ecosystems. Key Points: Marine net primary production is potentially predictable for at least 1 year in advance for many oceanic regions Regions where nutrients are the primary driver of net primary production are more predictable than light‐ or temperature‐driven regions The dynamic prediction system improves predictability of net primary production in some Large Marine Ecosystems over a persistence forecast